Peningkatan Efisiensi Administrasi Keuangan Melalui Sistem Penagihan Otomatis: Studi Kasus Pada PT Java Energy Semesta - Anggraeni, Deviana Kusnul; Widajantie, Tituk Diah (Forum Kerjasama Pendidikan Tinggi, 2025)
This study aims to analyze the impact of implementing an automated billing system based on Google Apps Script in enhancing the efficiency of financial administration processes at PT Java Energy Semesta. The study employs a descriptive qualitative method with a single case study approach, using data collection techniques such as direct observation, in-depth interviews with finance staff, and documentation of the system and billing activity logs. Data analysis was conducted thematically, including data reduction, categorization, and conclusion drawing, focusing on efficiency indicators such as the time required to prepare reminders, frequency of late payments, and the speed of customer confirmations. The results indicate that the implementation of the automated billing system successfully reduced the average time for processing daily billing reminders from 1–2 hours to under 10 minutes, decreased payment delays by up to 30%, and accelerated the financial information cycle. This automation also reduced dependency on administrative staff and improved the accuracy of information delivery. These findings imply that digitalizing administrative processes through simple and affordable platforms such as Google Apps Script can serve as an effective solution for medium-sized enterprises. In addition to streamlining workflows, the system also contributes to improved cash flow efficiency, stronger receivables control, and reduced credit risk, thereby supporting the overall financial stability of the company.